Pelatihan Penggunaan Trainer Solar Panel Untuk Guru Sekolah Menengah Kejuruan Teknik Ketenagalistrikan Sumatera Barat Menuju Era Energi Baru Terbarukan - Eliza, Fivia; Ambyar; Asnil; Delianti , Vera Irma; Myori, Dwiprima Elvanny; Sardi, Juli; Habibullah; Fadli, Radinal (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Teachers in vocational schools play an essential role in integrating renewable energy education into the curriculum, but limited tools and knowledge in assembling solar panels hinder practical learning. The program aims to provide teachers with practical knowledge and skills in assembling solar panels. Method: This activity was attended by productive teachers of SMK in the field of expertise in Electrical Power Installation Engineering throughout the province of West Sumatra. Activities are carried out in 4 stages, Preparation, Implementation, Monitoring, Evaluation, and Follow-up. Written tests and practical tests are conducted to find out the extent of the teacher's ability to use solar panel trainers. Result: The result of this program is an increase in knowledge and skills, teachers in solar panel assembly. This program contributes to trained teachers, to provide an interactive and interesting learning approach for students in the use of renewable energy. Conclusion: This training program not only meets the needs of education in facing the development of renewable energy technology, but also makes a real contribution in creating human resources who are ready to work in the renewable energy sector.